Study the role of personal factors on life satisfaction of nurses employed in ‎hospitals affiliated to Guilan University of Medical Sciences - Nastaran Mirfarhadi; Saghi Mousavi; Rasool Tabari; Ehsan Kazemnejhad leili (Journal of Holistic Nursing and Midwifery)
Introduction: Life satisfaction is primier purpose of human s life and it provides sufficient ‎basis for progress and confident basis to achieve higher levels. On the other hand, life ‎satisfaction brings out successes. Many studies have shown different factors such as ‎individual factors can affect life satisfaction. In attention to the role of nursing as key member ‎of healthcare, identifying effective factors on their satisfaction can have a direct effect on the ‎quality of healthcare and also on the society.‎